1974
DOI: 10.1111/j.1438-8677.1974.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Entomogenous Fungi From Ghana: Ii. The Genus Akanthomyces

Abstract: SUMMARY Four species of Akanthomyces, collected on various arthropod hosts in Ghana, are described and illustrated. Akanthomyces gracilis Samson & Evans spec. nov. appeared to occur on a wide variety of insect hosts and is particularly common on ants. Akanthomyces pistillariaeformis (Pat.) Samson & Evans comb. nov. (= Isaria pistillariaeformis Pat.) is often found on moths together with Cordyceps tuberculata. The variability in synnematous habit and the associated Cordyceps tuberculata is discussed. Akanthomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…While Hymenostilbe resembles Akanthomyces, however, a re-examination of the type specimens of several Hymenostilbe and Akanthomyces spp. has shown that the conidiogenous cells of the former are polyblastic, bearing solitary conidia on short denticles, whilst Akanthomyces is phialidic with conidia borne in basipetal chains (Samson & Evans 1974, 1975. The ITS phylograms clearly support the disparate positions of these two anamorph genera, that comes out in separate clades (II and IV).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…While Hymenostilbe resembles Akanthomyces, however, a re-examination of the type specimens of several Hymenostilbe and Akanthomyces spp. has shown that the conidiogenous cells of the former are polyblastic, bearing solitary conidia on short denticles, whilst Akanthomyces is phialidic with conidia borne in basipetal chains (Samson & Evans 1974, 1975. The ITS phylograms clearly support the disparate positions of these two anamorph genera, that comes out in separate clades (II and IV).…”
Section: Discussionmentioning
confidence: 78%
“…Taxa with clavate synnemata, such as in A. pistillariiformis (cfr clade II), were referred to the genus Insecticola (Mains 1950). This latter genus was not accepted by Samson & Evans (1974), who noted that the 'synnematous habit does not allow a clear delimitation between Akanthomyces and Insecticola', an opinion also concurred by HywelJones (1996a). The conidial chains in Akanthomyces are short and often difficult to observe, resulting in their frequently wrong placement in Hymenostilbe (Samson & Evans 1975).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations